1994
DOI: 10.2307/2491438
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Auditor Liability Rules

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 132.174.254.155 on Thu,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 11 publications
2
56
1
Order By: Relevance
“…Furthermore, the results are consistent with prior literature findings that present evidence of Big auditing firms increased audit quality (Simunic and Stein, 1987;Krishnan and Krishnan, 1996;Francis and Krishnan, 1999;Ireland and Lennox, 2002;Francis and Yu, 2009;Skinner and Srinivasan, 2012). Furthermore, the results concerning both industry expert auditors and the length of audit tenures are also supported by relevant literature (Chow and Rice, 1982;Citron and Taffler, 1992;Melumad and Thoman, 1990;Narayanan, 1994;Balsam et al, 2003;Krishnan, 2003Krishnan, , 2005Chi and Chin, 2011), implying their validity as determinants of audit quality.…”
Section: Multivariate Analysis Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the results are consistent with prior literature findings that present evidence of Big auditing firms increased audit quality (Simunic and Stein, 1987;Krishnan and Krishnan, 1996;Francis and Krishnan, 1999;Ireland and Lennox, 2002;Francis and Yu, 2009;Skinner and Srinivasan, 2012). Furthermore, the results concerning both industry expert auditors and the length of audit tenures are also supported by relevant literature (Chow and Rice, 1982;Citron and Taffler, 1992;Melumad and Thoman, 1990;Narayanan, 1994;Balsam et al, 2003;Krishnan, 2003Krishnan, , 2005Chi and Chin, 2011), implying their validity as determinants of audit quality.…”
Section: Multivariate Analysis Resultssupporting
confidence: 89%
“…According to this, the auditor might become less objective and/or apply less effort toward the detection of material misstatements (Arrunada and Paz-Ares, 1997). However, the issue of audit tenure and its relation to audit quality is a balancing act between the auditor's motivation to keep the audit-client relationship and to avoid any litigation risks, while protecting the audit firm's reputation and well established brand name (Chow and Rice, 1982;Citron and Taffler, 1992;Melumad and Thoman, 1990;Narayanan, 1994).…”
Section: Prior Literaturementioning
confidence: 99%
“…In a formal model, Narayanan (1994) has shown that under a proportionate liability regime (in which auditors pay only for their share of the damage), auditors have a stronger incentive to minimize litigation costs by working harder than under joint and several liability regimes (in which they pay there own damages plus those of insolvent codefendants). Audit quality is likely to increase under proportionality regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Our measurement of punishment severity combined three variables (negative effects for careers within company, dismissal from the firm, loss of accreditation as auditor). In the light of Narayanan's (1994) analysis, future research might use a more refined measure of firm level punishment regimes, disentangling the different kinds of incentive effects they might exert on individual auditors. This brings us to the possible limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, empirical research is not only inconclusive but also refers mainly to the US. Since litigation risk plays a major role in audit literature as a determinant of the auditor reporting decision (e.g., Melumad and Thoman, 1990;Narayanan, 1994), the relatively high-litigation risk of the US makes it difficult to extrapolate results to other settings 3 . In addition, most previous research has limited to examine the effects of tenure on the issuance of going-concern modified opinions (GCMO) to financially distressed firms.…”
Section: Introductionmentioning
confidence: 99%